Effectiveness of Intradialytic Stretching Exercises on Prevention and Reduction of Leg Muscle Cramps among Patients undergoing Hemodialysis: Randomized Controlled Trial - Amjed Abdulabbas Shraida; Diaa K. Abd-Ali; Hisham Q. Mohammad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Renal replacement therapy is a treatment option for people who have acute or chronic renal failure. A patientwith increasing symptoms of renal failure is referred to a dialysis and transplantation center early in thecourse of progressive kidney disease. Hemodialysis is one of the most widely used dialysis procedures.Muscle cramps are the most common complication experienced by hemodialysis patients that usuallydevelop during and in between hemodialysis therapy. These cramps appear to be the most common reasonfor the early termination of the hemodialysis session. Study Design: Pretest-posttest non-blind randomizedcontrolled trial has been used in the present study to evaluate the effectiveness of Intradialytic stretchingexercises on the leg muscle cramps among patients undergoing hemodialysis, from the period of September5th, 2020 to March 22nd, 2021. Study Sample: Non-probability purposive Sample of 60 patients undergoinghemodialysis. The sample is divided randomly into two groups; 30 patients as the study group and theother 30 as the control group. The setting of the study: The study is conducted in Al-Najaf City/Al-NajafAl-Ashraf Health Directorate / Al-Sadder Medical City / The specialized center for kidney diseases andtransplantation / Hemodialysis Unit. Result: The study result signifies that the level of muscle crampsimproved significantly among the study group participants compared with control group.